Auditoria de gestión a los programas implementados por el servicio ecuatoriano de capacitación profesional del cantón Francisco de Orellana, provincia de Orellana durante el primer semestre del año 2015 - Rivadeneira Sanmiguel, Janeth Erika (2016)
The development of the thesis: management audit the programs implemented by the Ecuadorian SERVICE PROFESSIONAL TRAINING Francisco de Orellana Canton, Orellana province DURING THE FIRST HALF OF THE YEAR 2015 is aimed at the study, implementation and verification of the fulfillment of the planned objectives by representatives of the aforementioned institution. The use of performance indicators which were of great help to determine compliance activities performed by employees within the parameters of efficiency and effectiveness with which it has developed to carry out the present study was required courses implemented by the Centre Orellana operation "SECAP". Also to carry out this thesis the use of methods, techniques and procedures was needed, which contributed with relevant information to understand the processes that are used in the Operating Center Orellana "SECAP" to offer training courses. In the development of this work was executed using the respective phases of the audit, ie preliminary knowledge was made up to the final report. From the results obtained from the performance audit determined that the institution does not apply management indicators that are vital for measuring the efficiency, effectiveness with which they develop their daily activities, for this reason it is recommended that the Service Ecuadorian Professional Training Orellana, periodically perform management audits in order that a new period to implement the corrective actions in order that their activities are met 100%. It could also ensure that the assistance of staff is done by firms on a record with the institution, this recording medium has led to staff put the firm when they see fit which makes noncompliance with the schedule, for this reason recommended the Operations Centre installing a biometric clock that help verify compliance with the time of entry and exit of personnel. Also it was found that the Operational Center Orellana "SECAP" does not make the dissemination of training courses throughout the province of Orellana, non-dissemination of training courses has led to the aforementioned institution does not have sufficient participants as a minimum requirement in each training, this situation has been recommended to the Operational Center Orellana through radio, television broadcast of the courses that are offered to the public is made. Upon completion of this research work was presented to the Coordinator of the Operations Centre a report which sets out the conclusions and valid, reasonable and appropriate recommendations to help improve management especially related to the programs implemented by the staff of the institution.